Exploration of the thoracoscopic treatment of esophageal atresia under high-frequency ventilation - Zheng, Chao; Lin, Yu; He, Yuanbin; Shen, Yong; Fan, Jiansen; Fang, Yifan (Frontiers in Pediatrics, 2022)
Objective: Explore the feasibility and safety of thoracoscopy in the treatment of esophageal atresia under high-frequency oscillatory ventilation (HFOV) mode. Methods: This was a single-center retrospective analysis. A total of 24 children were divided into the HFOV and the No-HFOV group. The demographic information, surgical results and relevant experience were analyzed. Results: All patients in the HFOV group underwent thoracoscopic esophageal atreplasty with a mean operation duration of 165.8±33.9 min. Two patients had postoperative anastomotic leakage, which was cured after conservative treatment. One child had a recurrent tracheoesophageal fistula, which was closed after endoscopic cauterization. The mean postoperative mechanical ventilation time was 8.83±8.02 days. There was no return of anastomotic leakage or r-TEF after oral feeding. Furthermore, there was no significant difference between the NO-HFOV and the HFOV groups except for the operation time where the HFOV group was shorter than that of the NO-HFOV group. Conclusion: Thoracoscopic esophageal atresia anastomosis under HFOV ventilation is feasible for patients with severe pulmonary infection, heart malformation, such as patent ductus arteriosus, ventricular septal defect, and poor anesthesia tolerance, but the long-term prognosis still needs further study in a large sample size.